A cluster analysis of reasons behind fear of birth among women in Sweden - Ingegerd Hildingsson; Margareta Johansson (Taylor & Francis Group, 2024)
AbstractBackground Fear of birth is common and complex, caused by a variety of reasons. The aim was to investigate the prevalence of pre-established reasons in relation to fear, and to identify profiles of women based on their reported reasons behind fear of birth.Methods A cross-sectional Swedish study of women with self-reported fear of birth who completed an online survey. Descriptive statistics, chi-square test, crude and adjusted odds ratios with 95% confidence intervals were used in the analysis of pre-established reasons in relation to self-reported severe fear. A Kappa-means cluster analysis was performed in order to group reasons, that were further investigated in relation to women's background variables.Results A total of 1419 women completed the survey. The strongest reason behind fear of birth was to be forced to give birth vaginally. Four clusters were identified and labeled: minor complexity (reference group), relative minor complexity, relative major complexity, and major complexity. Cesarean section preference, previous mental health problems, being younger, primiparity, and exposure to domestic violence were factors related to cluster grouping.Conclusions Women with fear of birth have various reasons and diverse complexities behind their fear. Health care providers need to investigate these reasons and support pregnant women with childbirth fear, based on their needs.